(untitled) (Bangladesh Journal of Botany, 2019)
In the present study, antibacterial and antioxidant (DPPH free radical scavenging activity) activity of an edible mushroom, Agaricus bisporus collected from Pakistan was investigated. In antibacterial assays, nhexane showed 4.83, 3.33, 16 and 3.33 mm inhibition zone diameter (IZD), chloroform showed 6.33, 16.17, 17 and 1.67 mm (IZD) while, ethyl acetate exhibited 30, 20, 19 and 28.67 mm (IZD) against four test plant pathogenic bacteria viz., Pseudomonas syringae Van Hall, Ralstonia solanacearum Yabuuchi et al. Xanthomonas axonopodis Dowson and Erwinia carotovora (Jones) Waldee, at 100 mg/ml concentration. Optical density (OD) was recorded at 517 nm. n-hexane extract showed 60.73, 47.6 and 33.05%, chloroform showed 89.97, 82.91 and 77.68% whereas, ethyl acetate exhibited 89.83, 65.82 and 23.59% free radical effects as compared to control. Gas chromatography mass spectrometry (GCMS) analysis showed the highest concentration of mono(2-ethylhexyl) phthalate.